PENGARUH SOSIALISASI PERPAJAKAN, PEMAHAMAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA MEDAN TIMUR - Br Ritonga, Asni Septiana; Jayusman, Sri Fitria; Tiara, Shita; Wibowo, M. Rizaldy (Worksheet : Jurnal Akuntansi, 2025)
This quantitative study, using a causal associative approach, was conducted on individual taxpayers at the East Medan Pratama Tax Office (KPP Pratama) who hold a Taxpayer Identification Number (NPWP). The purpose of this study is to determine the influence of tax socialization, taxpayer understanding and tax sanctions on taxpayer compliance at the East Medan Pratama Tax Office.This study used primary data. The population of this study was 212.615 individual taxpayers registered at the East Medan Pratama Tax Office in 2024, spread across three districts in Medan City. The sample consisted of 100 individual taxpayers, using a convenience sampling technique. A questionnaire was used for data collection. Data were analyzed using multiple linear regression, classical assumption testing, and hypothesis testing using SPSS version 25. The results of the classical assumption testing indicated that the research data met the criteria for normality, no multicollinearity, and no heteroscedasticity, thus ensuring a suitable regression model. The simultaneous test (F-test) indicated that all independent variables simultaneously or jointly influenced the dependent variable.